Fournier's gangrene with corpus spongiosum necrosis following obstructive emphysematous pyelonephritis: An exceptional and severe urological complication - EL Abidi Hamza; Ibrahimi Ahmed; Tariqi Reda; Mikou Mohammed Ali; Bennasser Abdallah; EL Sayegh Hashem; Nouini Yassine (Urology Case Reports)
Fournier's gangrene is a grave necrotizing fasciitis that primarily affects the perineum, spreading through the fascias and leading to significant tissue destruction. The involvement of the urethra in necrosis is extremely rare, if not anecdotal.Emphysematous pyelonephritis, is a urinary infection with a high risk of progression to sepsis. Although both Fournier's gangrene and obstructive pyelonephritis are independently well-documented, their concurrent presentation is uncommon and poses significant diagnostic and therapeutic challenges.In this report, we present a rare case of Fournier's gangrene secondary to emphysematous pyelonephritis, which further led to necrosis of the corpus spongiosum, a scarcely reported complication.